TEACHING ENGLISH FOR THE CLASSROOM: EFFECTIVE METHODOLOGIES AND CONTEMPORARY STRATEGIES (Journal of Universal Science Research, 2026)
This paper analyzes the primary methodologies in the field of English Language Teaching (ELT) and discusses their respective merits and drawbacks. Furthermore, it explores effective teaching strategies, the integration of technology, and the importance of learner-centered approaches to meet the diverse needs of language students in the contemporary classroom. The article offers practical advice and research-backed methods for educators.